Quantitative Variability, Heritability and Genetic Advance in Black gram by Effect of Mutation in Field Trail - L.Mullainathan, D. Arulbalachandran (Journal of Phytology, 2009)
Genetic variation has led to an increasing the quantitative traits of crops. The variability on genome is induced by mutation, which enhances the productivity. We evaluated variability on quantitative characters such as, plant height, number of branches/plant, number of leaves/plant, number of fruit clusters/plant, number of pods/plant, number of seeds/pod, yield/plant and 100 seed weight of black gram in M2 generation by the effect of mutation by gamma rays. The results were showed high genetic variability, heritability and genetic advance with significant enhancement (P 0.05 and P 0.01) in growth and yield traits. Hence selection is effective for these traits could be possible through gamma rays. The speculation of effects of gamma rays on genome is that irradiation, induced addition, deletion in DNA pairs and also attributed large chromosomal rearrangement. The result were showed significant enhancement in yield and related traits. It indicates that improvement in quantitative traits would be possible through gamma rays.